Voz, afecto y representación nahua en la canción vernácula del siglo XVII - Chávez Bárcenas, Ireri Elizabeth (El Colegio de México, A.C., 2021)
The four Nahuatl Christmas carols composed by Gaspar Fernández in Puebla between 1610 and 1614 have enjoyed a renewed popularity in recent decades, but little attention has been paid to their singular representation of natural Indians or their possible meanings. In these songs, Indians are represented as humble shepherds who sympathize with Christ’s suffering, a particularly interesting image when put into the context of the intense debate on the exploitation of the indigenous population in the textile industry, which was undermining the legitimacy of the overseas expansion of the Spanish Empire in the late 16th Century.The artistic representation of marginalized groups in New Spain offers a valuable opportunity to reflect on the possible motivations that inspired these devotional songs, whether they be theological, political or social. This article shows the way in which the conditions imposed upon the region’s natural Indians were reflected in certain poetic/musical genres in the early 17th Century. Beyond the identification of evident stereotypes or literary conventions, a detailed analysis of these four Nahuatl songs composed by Fernández sheds new light on the use of poverty and suffering as emblematic of the natural Indian in vernacular devotional songs.